Credentialing in Pharmacy Practice: Examining Pharmacist Views and Perceptions - Sun Lee; Nancy Dao; Micah Hata; Anandi Law (University of Minnesota Libraries Publishing, 2019)
Introduction: Pharmacy practice has evolved to include direct patient care and interprofessional team models. Proper documentation of training and certification is required to verify eligibility for providing specialized services and for reimbursement. Objectives: The objectives of this study were to assess pharmacists' views and perceptions on credentialing with respect to (1) familiarity and perceived importance of credentialing; (2) satisfaction with current credentialing tracking systems; and (3) challenges in adopting a centralized credentialing platform. Methods: This study used a cross-sectional, survey design to examine pharmacist perceptions of credentialing. The survey, distributed by the American Pharmacists Association from November 18, 2017 to December 2, 2017, consisted of 11 demographic items and 22 items about familiarity, importance, satisfaction and current systems of credentialing in pharmacy practice. Descriptive statistics were used to characterize the sample and outcome variables. Content analysis was conducted on freeform responses. Results: Data were analyzed from 446 (7.3%) completed surveys of the 6,144 distributed. Respondents were primarily represented by pharmacists from chain stores (29.6%), outpatient clinics (16.6%), and academic settings (15.2%). Job titles included staff pharmacist (33.9%), clinical pharmacist (21.3%), and manager positions (18.3%). Nine of 10 pharmacists reported familiarity with credentialing and considered credentialing as important to the pharmacy profession. Majority agreed with the importance of having a centralized online platform to store credentialing information (96.1%) and to obtain reimbursement (97.1%). Poor integration of data among different platforms (16%) was a common reason for dissatisfaction with current tracking systems. Most respondents (96.5%) were willing to provide information necessary for credentialing; however, over half were concerned about security of the information. Conclusions: This study was among the first to examine pharmacist perceptions of credentialing. Pharmacists in this study were familiar with and responsive to participating in credentialing process. They were also supportive of having a centralized credentialing system, but held reservations about security of information.   Article Type: Original Research